Kompetensi Kepribadian Guru Sebagai Role Model Dalam Peningkatan Akhlak Siswa Mas Insan Kesuma Madani Namorambe Deli Serdang - Parida Hannum Siregar; Hasnil Aida Nasution; Nurul Hidayah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the competence of teachers’ personalities as role models in improving students’ morals at MAS Insan Kesuma Madani Namorambe Deli Serdang. The research focuses on teachers’ personality competence, students’ moral behavior, and the supporting and inhibiting factors influencing teachers’ role modeling. This qualitative descriptive study collected data through interviews with two teachers, the principal, the vice principal, and five eleventh-grade students in May 2025. The findings reveal that teachers demonstrate good personality competence through consistent attitudes and effective communication, positively impacting students’ moral development. However, students’ morals vary; some exhibit good behavior while others show less optimal conduct. Supporting factors include a conducive school environment, ongoing teacher training, and collaboration with students’ families. Inhibiting factors consist of teachers’ heavy workloads, negative influences from social media and peer environments, and limited school facilities. The study recommends enhancing teacher support, strengthening school-family collaboration, and addressing external influences to optimize teachers’ roles as role models in shaping students’ character.